Salmonella enterica Serovar Typhimurium-Induced Maturation of Bone Marrow-Derived Dendritic Cells - Svensson, Mattias (American Society for Microbiology, 2000)
Murine bone marrow-derived dendritic cells (DC) can phagocytose and process Salmonella enterica serovar Typhimurium for peptide presentation on major histocompatibility complex class I (MHC-I) and MHC-II molecules. To investigate if a serovar Typhimurium encounter with DC induces maturation and downregulates their ability to present antigens from subsequently encountered bacteria, DC were pulsed with serovar Typhimurium 24 h prior to coincubating with Escherichia coli expressing the model antigen Crl-OVA. Quantitating presentation of OVA epitopes contained within Crl-OVA showed that Salmonella-pulsed DC had a reduced capacity to process Crl-OVA-expressing E. coli for OVA(257-264)/K(b) and OVA(265-277)/I-A(b) presentation. In addition, time course studies of DC pulsed with Crl-OVA-expressing serovar Typhimurium showed that OVA(257-264)/K(b) complexes could stimulate CD8OVA T-hybridoma cells for <24 h following a bacterial pulse, while OVA(265-277)/I-A(b) complexes could stimulate OT4H T-hybridoma cells for >24 but <48 h. The phoP-phoQ virulence locus of serovar Typhimurium also influenced the ability of DC to process Crl-OVA-expressing serovar Typhimurium for OVA(265-277)/I-A(b) presentation but not for OVA(257-264)/K(b) presentation. Furthermore, pulsing of DC with serovar Typhimurium followed by incubation for 24 or 48 h altered surface expression of MHC-I, MHC-II, CD40, CD54, CD80, and CD86, generating a DC population with a uniform, high expression level of these molecules. Finally, neither the serovar Typhimurium phoP-phoQ locus nor lipopolysaccharides (LPS) containing lipid A modifications purified from phoP mutant strains had a different effect on DC maturation from that of wild-type serovar Typhimurium or purified wild-type LPS. Thus, these data show that Salmonella or Salmonella LPS induces maturation of DC and that this process is not altered by the Salmonella phoP virulence locus. However, phoP did influence OVA(265-277)/I-A(b) presentation by DC infected with Crl-OVA-expressing serovar Typhimurium when quantitated after 2 h of bacterial infection.